KAJIAN KADAR FENOLAT DAN AKTIVITAS ANTIOSIDAN JUS KULIT BUAH SEMANGKA (CITRULLUS LANATUS) - Ismayanti, Ismayanti; Bahri, Syaiful; Nurhaeni, Nurhaeni (Univ. Tadulako, 2013)
This research aim to determine rate of total phenolic and activity of antioxidant of ellipse and circular watermelon peel juice. Method which used in examination of rate total phenolic that is method of Folin_Ciocalteu and activity of antioxidant use method of DPPH. Result of which is obtained from examination rate of phenolic circularwatermelon peel heavily 1,4 kg is 18,702% and ellipse watermelon peel heavily is 1,9 kg is 19,168%. Activity of antioxidant with value of IC50 of circular watermelon 214,369 ppm and ellipse watermelon 376,266 ppm. Base on value of IC50, both of sample that mentioned appertained weak antioxidant.